Web-Based Pencak Silat Championship Registration Information System: Indonesia - Gunawan Eka Putra; Budi Apriyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Obtaining information about the championship has not been through digital online so that participants have to wait until the championship proposal is distributed to schools. Registration for the pencak silat championship is still through the conventional system by coming to the registration site so that prospective participants need more time. The championship participant data processing management system is not yet based on a website, so the committee must register the participants manually. The method used in the development of this software uses the waterfall model which is divided into five stages, namely Analysis of software requirements, Design, Program Code Generation, Testing and Support (support) or Maintenance (maintenance). The results of this system design can facilitate the Padjadjaran Family Cimande (KBPC) in recording, processing and registration information for data management purposes as well as recapitulation of championship registration reports. Prospective participants do not need to come to the registration site, just go online. So that the committee can collect data easily. Keyword: System Design, Registration, Pencak Silat, WEB-Based.